Watch out for snakes! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Snake bites are 10 to 20 times more common in rural than in urban areas. The incomplete data available shows that there are about one million snake bites a year in Africa, with 600,000 cases of poisoning and 20,000 deaths...